58 Anticipatory prescribing for continuous sub-cutaneous infusion: friend or foe?. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Benson, Sinead; Cadwallader, Claire; Cartwright-Terry, Teena; Cooper, Malcolm; Monnery, Daniel; Finnegan, Clare; Giles, Robert; Sadiq, Rehana; Watson, Amanda
Abstract : Background: Anticipatory prescribing of 'prn' medication for symptom control is recommended for those approaching the last week-of-life however practices regarding anticipatory prescribing for continuous subcutaneous infusions (CSCI) varies widely. The Gosport Report highlighted risks associated with anticipatory prescribing for CSCI. The Association of Supportive & Palliative Care Pharmacy state the perceived benefit does not outweigh the risks. Methods: A network-wide cross-boundary audit was undertaken of the use of CSCIs in patients known to specialist palliative care services. A survey was completed by each service-lead and feedback collated following presentation of results. Results: 208 of 347 patients (174 hospital, 49 community, 124 hospice) prescribed medication via a CSCI were recognised as likely to be dying. Drugs prescribed included strong opioids (286) anti-emetics (133), anxiolytics (89), anti-cholinergics (102), anticonvulsants (20) and steroids (6). Median doses of opioids and benzodiazepines were low (e, g, morphine 10 mg CSCI q24h) The CSCI had been prescribed in anticipation in 1/5 of patients across all care settings (hospital 20, hospice 24, community 16). 58% of services/organisations responding to the survey allow prescribing for CSCI in anticipation. Feedback following presentation of results and proposed guideline highlighted two conflicting sets of views and practices: anticipatory prescribing for CSCI as vital to ensure timely symptom control in the dying vs. the view it is unsafe practice, citing incidents/near-misses resulting from lack of clinical assessment of need at the time a CSCI is commenced. This audit reviewed current practice but is unlikely to capture such clinical incidents or 'near-misses' where drugs are administered without indication or at high doses. Conclusion: There is conflicting practice and opinion surrounding the risks and benefits of anticipatory prescribing for CSCI. This audit did not identify unsafe practice but will not reliably capture incidents or near-misses. Further evidence-based national guidance is required to guide safe practice.